Beyond Balancing? China's Quest For Security and Power in East Asia. (4th August 2013) - Lim, Yves‐Heng
Abstract : Observing the evolution of China's interaction with its international environment, Zhang Baijia argued that the advent of the Xinhai Revolution marked the beginning of China's participation in the modern interstate system. Becoming a more "normal" player after seven decades of foreign aggressions and encroachments, China could hardly have been more aware of the realist rule that, in an anarchic international environment, security can never be taken for granted. The lesson regarding the price of weakness had lasting consequences for China, and, by the end of the century, China had become, in Thomas Christensen's words, "the high church of realpolitik in the post‐Cold War world."